การศึกษาปริมาณที่เหมาะสมของน้ำหมักชีวภาพจากเศษวัสดุอินทรีย์ต่อการเจริญเติบโตของพืชผัก - อัจฉริยมนตรี อัตต์; สุทธิภาศิลป์ รัชนีพร; วิชิต นริศรา (Community and Social Development Journal, 2011)
บทคัดย่อภาษาไทยไม่สมบูรณ์ Study on Suitable Content of Bio-extracted Solution from Organic Residue on Vegetables Growth The objective of this research was to study on nutrient availability and number of effective micro-organism and study relationship between suitable content of bio-extracted and number of application days on vegetables growth and yield. Bio-extracted solution made from vegetable and fruit residue, fresh milk, black-strap molasses, rice bran and effective micro-organism solution (MMO) mixed with air pump and manual rotation every day until to 2 month that prompts to use. The concentration of plant nutrient in bio-extract solution each pH, EC, nitrogen (N), phosphorus (P), potassium (K), calcium (Ca) and magnesium (Mg) and sulfer (S) was 3.77, 18.7 dc/m., 0.13, 0.08, 0.57, 0.11, 0.12 0.55 % weight respectively. However, the nutrients analysis in organic bio-extract was founded in the range of organic liquid fertilizer standard in Department of Agriculture. So, we can use in organic farming. The statistical model was 7×3 factorial in randomized complete block design and 3 replication comprised of two factors as spray rate were 0, 10, 20, 25, 30, 35 and 40 cc./20 liter of water and frequency were 3, 5 and 7 day/application. The collecting data as height, leaf length, leaf wide, number of flower, number of fruits and fruit weight. The result found that bio-extract solution at 40 cc/20 liter of water gave the best result in significantly different on growth and yield. In term of weight of tomato (Lycopesicon esculentum var. seeda), Chinese kale (Brassica oleracea var. alboglabra) and cos lettuce (Lactuca sativa var. Longifolla) were 470.00, 169.11 and 233.33 g/plant, respectively, correlation coefficient was 0.8330, 0.9034 and 0.7597, respectively. For pak choi (Brassica chinensis var. chinensis), the result revealed that bio-extract solution at 30 cc/20 liter of water gave the best result in significantly different. In term of weight was 147.78 g/plant, correlation coefficient was 0.7742. In addition, frequency for application was effect on growth and yield for pak choi and Chinese kale in significantly different. After finish the experiment, we were setting up a workshop and public community learning exchange together. And we were founded the most of leader farmers produce and use bio-extract solution with very positive results include that it reduces the need for money to buy chemical fertilizer and recycles local waste materials.